On the stochastic bit–rock interaction disturbances and its effects on the performance of two commercial control strategies used in drill strings. (1st February 2022) - Lobo, D.M.; Ritto, T.G.; Castello, D.A.; Batou, A.
Abstract: The vibration of drill strings is a well-known source of undesirable disturbance in drilling operation, therefore it is important to design and evaluate active controllers to suppress it. The drill string dynamics is complex due to nonlinear interactions with the environment, and the uncertainties related to them. This paper aims to analyze two commercial control strategies acting at the top drive, namely stiff controller and SoftSpeed, applied to a pure torsional drill string model that takes into account uncertainties in the bit–rock interaction. The model is calibrated with field data and the numerical results present a good agreement with the measurements. Uncertainties in the torsional vibration severity are assessed through severity maps. Finally, the effect of the uncertainty level on the control strategies is analyzed. Although SoftSpeed gives better results, it is clear that the controller becomes less effective in suppressing vibrations as the uncertainties increases. Highlights: Calibration of a stochastic model describing the uncertainties in bit–rock interaction. Performance analysis of two commercial controllers in the presence of uncertainties. SoftSpeed is more efficient in mitigating vibration for all the cases considered. Controllers lose efficiency in the presence of higher levels of uncertainties.